High-cohesiveness ceramic tile adhesive
By using silicate cement, quartz sand, bentonite, multi-copolymerizable redispersible glue powder and cellulose ether formulas in ceramic tile glue, the problem of insufficient bonding strength after thermal aging of ceramic tile glue is solved, and higher adhesion is achieved The strength and stability of the tile avoid hollowing and falling off.
Patent Information
- Application Number
- CN202310804333.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-03
- Publication Date
- 2025-01-03
AI Technical Summary
The bonding strength of existing ceramic tile glue is unqualified after thermal aging, resulting in cracks during thermal expansion and contraction of ceramic tiles at different temperatures, gradually forming hollowing and causing falloff, especially in external wall tiling projects.
Using a high bonding ceramic tile glue formula, including silicate cement, quartz sand, bentonite, multi-copolymerizable redispersible glue powder, hydrophobic agent and cellulose ether, through specific cellulose ether preparation methods and quartz sand particle size Control and enhance the adhesion and stability of ceramic tile adhesive.
It effectively improves the bonding strength and stability of ceramic tile glue, and through the chemical bond between cellulose ether and cement mortar, the adhesive effect of ceramic tile glue is enhanced and cracks and shedding problems are avoided.
Smart Images

Figure BDA0004317209420000071
Abstract
Description
Technical Field
[0001] The invention relates to the field of tile adhesive preparation, and in particular to a high-adhesive tile adhesive. Background Art
[0002] Although there are many tile adhesive products on the market, there are a considerable number of products that do not meet the quality standards of tile adhesives. Industry standard JC / T 547-2017 The requirements are specifically reflected in the fact that a considerable number of products have unqualified bonding strength after thermal aging. Some tile tiling projects, especially exterior wall tiling projects, even if the thin layer method and tile adhesive products are used, still have hollowing and falling of tiles after a few years of use. A very important reason is that the bonding strength of the tile adhesive is not good after thermal aging, that is, when the tiles expand and contract at different temperature fields, small cracks will eventually appear between the tile adhesive and the tiles. When these cracks accumulate to a certain number, they will gradually form hollows and eventually fall off. Summary of the invention
[0003] A method for preparing a high-adhesive tile adhesive is provided to solve the problem of how to increase the viscosity. To achieve the above purpose, the present invention adopts the following technical solutions:
[0004] A high-adhesive tile adhesive, comprising the following formula in parts by weight: 130-140 parts of silicate cement, 130-140 parts of quartz sand, 50-60 parts of bentonite, 30-40 parts of multi-polymerized redispersible adhesive powder, 11-14 parts of water repellent, 6-7 parts of cellulose ether, and 3-4 parts of polycarboxylic acid water reducer;
[0005] The preparation method of the cellulose ether comprises the following steps:
[0006] S1. Cellulose pretreatment: The raw material bamboo nanocellulose is crushed and then put into the equipment for softening. The raw material cellulose is then pre-alkylated with halogenated hydrocarbons.
[0007] S2. Etherification reaction: The pretreated cellulose undergoes an etherification reaction to generate ether bonds to form cellulose ether.
[0008] 1) Preparation of alkali cellulose: cellulose is boiled in alkali solution for 20-30 minutes;
[0009] 2) Etherification, etherification reaction of alkali cellulose with sodium chloroacetate;
[0010] 3) Neutralize the unreacted base with acid.
[0011] 4) Product separation and post-processing to obtain cellulose ether.
[0012] S3. Cleaning and drying: The product after the reaction is washed several times to remove unreacted raw materials and reaction by-products, etc.; finally, it is dried to obtain cellulose ether.
[0013] Furthermore, the method for producing bamboo nanocellulose in step S1 is as follows:
[0014] The bamboo is collected from the Zigong area of Yibin, Sichuan. After removing the green and yellow parts of the bamboo, the bamboo pieces are ground into bamboo powder of 0.16-0.22mm.
[0015] First, the bamboo powder was subjected to Soxhlet extraction in a mixed solution of V (toluene): V (ethanol) = 2:1 for 12 hours to remove the extract in the bamboo material, and then treated with acidic sodium chlorite (pH 4.5-5) at 80°C for 1 hour. This process was repeated 6-8 times to remove the lignin component, and then washed with distilled water until neutral and dried to obtain holocellulose. The obtained holocellulose was placed in a 5% sodium hydroxide solution and stirred evenly at 80°C for 2.5 hours, then washed with distilled water until neutral, and dried to obtain α-cellulose;
[0016] α-cellulose was put into 64% sulfuric acid solution in a certain proportion and stirred evenly at 40°C for 45 min, and a certain proportion of distilled water was added to terminate the reaction; then, nanocellulose suspension was obtained after dialysis, ultrasonic dispersion and centrifugation, and finally, bamboo nanocellulose was obtained after freeze-drying.
[0017] Furthermore, the particle size of the quartz sand is 200-300.
[0018] In summary, this application has the following beneficial effects:
[0019] 1. The present invention relates to a high-adhesive tile adhesive, which is prepared by using cellulose ether and multi-polymerized redispersible adhesive powder, and can effectively improve the adhesiveness of the tile adhesive, etc. In addition, bentonite has good miscibility, which can make the raw materials in the tile adhesive evenly distributed, thereby increasing the stability of the performance of the tile adhesive.
[0020] The cellulose ether and the water repellent contained in the tile adhesive of the present invention can effectively penetrate into the cement mortar, and form bonds with the cement mortar molecules and the tile backing through the action of van der Waals force, hydrogen bond or chemical bond, thereby enhancing the adhesion of the tile adhesive and making it have a good adhesive effect. DETAILED DESCRIPTION
[0021] The present application is further described in detail below with reference to the embodiments.
[0022] Embodiment 1: A high-adhesive tile adhesive, comprising the following formula in parts by weight: 130-140 parts of silicate cement, 130-140 parts of quartz sand, 50-60 parts of bentonite, 30-40 parts of multi-polymerized redispersible rubber powder, 11-14 parts of water repellent, 6-7 parts of cellulose ether, and 3-4 parts of polycarboxylic acid water reducer;
[0023] The preparation method of the cellulose ether comprises the following steps:
[0024] S1. Cellulose pretreatment: The raw material bamboo nanocellulose is crushed and then put into the equipment for softening. The raw material cellulose is then pre-alkylated with halogenated hydrocarbons.
[0025] S2. Etherification reaction: The pretreated cellulose undergoes an etherification reaction to generate ether bonds to form cellulose ether.
[0026] 1) Preparation of alkali cellulose: cellulose is boiled in alkali solution for 20-30 minutes;
[0027] 2) Etherification, etherification reaction of alkali cellulose with sodium chloroacetate;
[0028] 3) Neutralize the unreacted base with acid.
[0029] 4) Product separation and post-processing to obtain cellulose ether.
[0030] S3. Cleaning and drying: The product after the reaction is washed several times to remove unreacted raw materials and reaction by-products, etc.; finally, it is dried to obtain cellulose ether.
[0031] Furthermore, the method for producing bamboo nanocellulose in step S1 is as follows:
[0032] The bamboo is collected from the Zigong area of Yibin, Sichuan. After removing the green and yellow parts of the bamboo, the bamboo pieces are ground into bamboo powder of 0.16-0.22mm.
[0033] First, the bamboo powder was subjected to Soxhlet extraction in a mixed solution of V (toluene): V (ethanol) = 2:1 for 12 hours to remove the extract in the bamboo material, and then treated with acidic sodium chlorite (pH 4.5-5) at 80°C for 1 hour. This process was repeated 6-8 times to remove the lignin component, and then washed with distilled water until neutral and dried to obtain holocellulose. The obtained holocellulose was placed in a 5% sodium hydroxide solution and stirred evenly at 80°C for 2.5 hours, then washed with distilled water until neutral, and dried to obtain α-cellulose;
[0034] α-cellulose was put into 64% sulfuric acid solution in a certain proportion and stirred evenly at 40°C for 45 min, and a certain proportion of distilled water was added to terminate the reaction; then, nanocellulose suspension was obtained after dialysis, ultrasonic dispersion and centrifugation, and finally, bamboo nanocellulose was obtained after freeze-drying.
[0035] Furthermore, the particle size of the quartz sand is 200-300.
[0036] Embodiment 2:
[0037] A high-adhesive tile adhesive, comprising the following formula in parts by weight: 130 parts of silicate cement, 130 parts of quartz sand, 50 parts of bentonite, 30 parts of multi-polymerized redispersible adhesive powder, 11 parts of water repellent, 6 parts of cellulose ether, and 3 parts of polycarboxylic acid water reducer;
[0038] The preparation method of the cellulose ether comprises the following steps:
[0039] S1. Cellulose pretreatment: The raw material bamboo nanocellulose is crushed and then put into the equipment for softening. The raw material cellulose is then pre-alkylated with halogenated hydrocarbons.
[0040] S2. Etherification reaction: The pretreated cellulose undergoes an etherification reaction to generate ether bonds to form cellulose ether.
[0041] 1) Preparation of alkali cellulose: cellulose is boiled in alkali solution for 20-30 minutes;
[0042] 2) Etherification, etherification reaction of alkali cellulose with sodium chloroacetate;
[0043] 3) Neutralize the unreacted base with acid.
[0044] 4) Product separation and post-processing to obtain cellulose ether.
[0045] S3. Cleaning and drying: The product after the reaction is washed several times to remove unreacted raw materials and reaction by-products, etc.; finally, it is dried to obtain cellulose ether.
[0046] Furthermore, the method for producing bamboo nanocellulose in step S1 is as follows:
[0047] The bamboo is collected from the Zigong area of Yibin, Sichuan. After removing the green and yellow bamboo, the bamboo pieces are ground into 0.16mm bamboo powder.
[0048] First, the bamboo powder was subjected to Soxhlet extraction in a mixed solution of V (toluene): V (ethanol) = 2:1 for 12 hours to remove the extract in the bamboo material, and then treated with acidic sodium chlorite (pH 4.5-5) at 80°C for 1 hour. This process was repeated 6-8 times to remove the lignin component, and then washed with distilled water until neutral and dried to obtain holocellulose. The obtained holocellulose was placed in a 5% sodium hydroxide solution and stirred evenly at 80°C for 2.5 hours, then washed with distilled water until neutral, and dried to obtain α-cellulose;
[0049] α-cellulose was put into 64% sulfuric acid solution in a certain proportion and stirred evenly at 40°C for 45 min, and a certain proportion of distilled water was added to terminate the reaction; then, nanocellulose suspension was obtained after dialysis, ultrasonic dispersion and centrifugation, and finally, bamboo nanocellulose was obtained after freeze-drying.
[0050] Furthermore, the particle size of the quartz sand is 200.
[0051] Embodiment three:
[0052] A high-adhesive tile adhesive, comprising the following formula in parts by weight: 140 parts of silicate cement, 140 parts of quartz sand, 60 parts of bentonite, 40 parts of multi-polymerized redispersible adhesive powder, 14 parts of water repellent, 7 parts of cellulose ether, and 4 parts of polycarboxylic acid water reducer;
[0053] The preparation method of the cellulose ether comprises the following steps:
[0054] S1. Cellulose pretreatment: The raw material bamboo nanocellulose is crushed and then put into the equipment for softening. The raw material cellulose is then pre-alkylated with halogenated hydrocarbons.
[0055] S2. Etherification reaction: The pretreated cellulose undergoes an etherification reaction to generate ether bonds to form cellulose ether.
[0056] 1) Preparation of alkali cellulose: cellulose is boiled in alkali solution for 20-30 minutes;
[0057] 2) Etherification, etherification reaction of alkali cellulose with sodium chloroacetate;
[0058] 3) Neutralize the unreacted base with acid.
[0059] 4) Product separation and post-processing to obtain cellulose ether.
[0060] S3. Cleaning and drying: The product after the reaction is washed several times to remove unreacted raw materials and reaction by-products, etc.; finally, it is dried to obtain cellulose ether.
[0061] Furthermore, the method for producing bamboo nanocellulose in step S1 is as follows:
[0062] The bamboo is collected from the Zigong area of Yibin, Sichuan. After removing the green and yellow bamboo, the bamboo pieces are ground into 0.22mm bamboo powder.
[0063] First, the bamboo powder was subjected to Soxhlet extraction in a mixed solution of V (toluene): V (ethanol) = 2:1 for 12 hours to remove the extract in the bamboo material, and then treated with acidic sodium chlorite (pH 4.5-5) at 80°C for 1 hour. This process was repeated 6-8 times to remove the lignin component, and then washed with distilled water until neutral and dried to obtain holocellulose. The obtained holocellulose was placed in a 5% sodium hydroxide solution and stirred evenly at 80°C for 2.5 hours, then washed with distilled water until neutral, and dried to obtain α-cellulose;
[0064] α-cellulose was put into 64% sulfuric acid solution in a certain proportion and stirred evenly at 40°C for 45 min, and a certain proportion of distilled water was added to terminate the reaction; then, nanocellulose suspension was obtained after dialysis, ultrasonic dispersion and centrifugation, and finally, bamboo nanocellulose was obtained after freeze-drying.
[0065] Furthermore, the particle size of the quartz sand is 300 mesh.
[0066] Embodiment 4:
[0067] A high-adhesive tile adhesive, comprising the following formula in parts by weight: 135 parts of silicate cement, 135 parts of quartz sand, 55 parts of bentonite, 35 parts of multi-polymerized redispersible adhesive powder, 12 parts of water repellent, 6.5 parts of cellulose ether, and 3.5 parts of polycarboxylic acid water reducer;
[0068] The preparation method of the cellulose ether comprises the following steps:
[0069] S1. Cellulose pretreatment: The raw material bamboo nanocellulose is crushed and then put into the equipment for softening. The raw material cellulose is then pre-alkylated with halogenated hydrocarbons.
[0070] S2. Etherification reaction: The pretreated cellulose undergoes an etherification reaction to generate ether bonds to form cellulose ether.
[0071] 1) Preparation of alkali cellulose: cellulose is boiled in alkali solution for 20-30 minutes;
[0072] 2) Etherification, etherification reaction of alkali cellulose with sodium chloroacetate;
[0073] 3) Neutralize the unreacted base with acid.
[0074] 4) Product separation and post-processing to obtain cellulose ether.
[0075] S3. Cleaning and drying: The product after the reaction is washed several times to remove unreacted raw materials and reaction by-products, etc.; finally, it is dried to obtain cellulose ether.
[0076] Furthermore, the method for producing bamboo nanocellulose in step S1 is as follows:
[0077] The bamboo is collected from the Zigong area of Yibin, Sichuan. After removing the green and yellow parts of the bamboo, the bamboo pieces are ground into bamboo powder of 0.16-0.22mm.
[0078] First, the bamboo powder was subjected to Soxhlet extraction in a mixed solution of V (toluene): V (ethanol) = 2:1 for 12 hours to remove the extract in the bamboo material, and then treated with acidic sodium chlorite (pH 4.5-5) at 80°C for 1 hour. This process was repeated 6-8 times to remove the lignin component, and then washed with distilled water until neutral and dried to obtain holocellulose. The obtained holocellulose was placed in a 5% sodium hydroxide solution and stirred evenly at 80°C for 2.5 hours, then washed with distilled water until neutral, and dried to obtain α-cellulose;
[0079] α-cellulose was put into 64% sulfuric acid solution in a certain proportion and stirred evenly at 40°C for 45 min, and a certain proportion of distilled water was added to terminate the reaction; then, nanocellulose suspension was obtained after dialysis, ultrasonic dispersion and centrifugation, and finally, bamboo nanocellulose was obtained after freeze-drying.
[0080] Furthermore, the particle size of the quartz sand is 250.
[0081] According to the products obtained in Example 2 to Example 4, a bonding test of tile adhesive bonding strength was carried out on the products.
[0082]
[0083] Tile adhesive bonding strength test:
[0084] 1. Experimental equipment.
[0085] Putty knife, stirrer, palette knife, 547 standard ceramic brick (50mm*50mm), mortar block (70mm*70mm*20mm)
[0086] Bond strength puller, AB glue, tile glue, special putty knife with teeth (6mm) for tile glue, 2kg weight.
[0087] 2. Steps of experiment
[0088] 1. Accurately weigh 1000g of tile adhesive in an appropriate container, add the standard amount of water, stir evenly with a stirrer (stir for about 2min) and set aside.
[0089] 2. Use a palette knife to evenly apply a thin layer of tile adhesive on the wide surface of the mortar block, then use a putty knife to scrape about 6mm of tile adhesive on the mortar block, and then use a toothed putty knife to scrape out strips of tile adhesive vertically against the mortar block. Let it stand for 5 minutes.
[0090] 3. Continue with the previous step and place the standard tile in the center of the mortar block. Press a 2kg weight on the center of the tile for 30 seconds, then remove the object and use a palette knife to scrape off the excess tile glue around the tile.
[0091] 4. Repeat the above steps to make 6 pieces as a group. Then cure under standard conditions.
[0092] 3. Determination of bonding strength
[0093] 1. One day before the curing time, take out the test block, use AB glue to bond the pull-out block and the tile (test block), and put it back for curing after the glue solidifies.
[0094] 2. Use a puller to measure the bonding strength data and record it.
[0095] 3. Remove the highest and lowest values, calculate the pulling data, and analyze the experimental conclusions.
[0096] The embodiments of the present application are merely explanations of the present application and are not limitations of the present application. After reading this specification, those skilled in the art may make modifications to the embodiments without any creative contribution as needed. However, as long as they are within the scope of the claims of the present application, they will be protected by the patent law.
Claims
1. A high-adhesive tile adhesive, characterized in that it comprises the following formula in parts by weight: 130-140 parts of silicate cement, 130-140 parts of quartz sand, 50-60 parts of bentonite, 30-40 parts of multi-polymerized redispersible rubber powder, 11-14 parts of water repellent, 6-7 parts of cellulose ether, and 3-4 parts of polycarboxylic acid water reducer; The preparation method of the cellulose ether comprises the following steps: S1. Cellulose pretreatment: The raw material bamboo nanocellulose is crushed and then put into the equipment for softening. The raw material cellulose is then pre-alkylated with halogenated hydrocarbons. S2. Etherification reaction: The pretreated cellulose undergoes an etherification reaction to generate ether bonds to form cellulose ether. 1) Preparation of alkali cellulose: cellulose is boiled in alkali solution for 20-30 minutes; 2) Etherification, etherification reaction of alkali cellulose with sodium chloroacetate; 3) Neutralize the unreacted base with acid. 4) Product separation and post-processing to obtain cellulose ether. S3. Cleaning and drying: The product after the reaction is washed several times to remove unreacted raw materials and reaction by-products, etc.; finally, it is dried to obtain cellulose ether.
2. A high-adhesion tile adhesive according to claim 1, characterized in that: The method for producing bamboo nanocellulose in step S1 is as follows: The bamboo is collected from the Zigong area of Yibin, Sichuan. After removing the green and yellow parts of the bamboo, the bamboo pieces are ground into bamboo powder of 0.16-0.22mm. First, the bamboo powder was subjected to Soxhlet extraction in a mixed solution of V (toluene): V (ethanol) = 2:1 for 12 hours to remove the extract in the bamboo material, and then treated with acidic sodium chlorite (pH 4.5-5) at 80°C for 1 hour. This process was repeated 6-8 times to remove the lignin component, and then washed with distilled water until neutral and dried to obtain holocellulose. The obtained holocellulose was placed in a 5% sodium hydroxide solution and stirred evenly at 80°C for 2.5 hours, then washed with distilled water until neutral, and dried to obtain α-cellulose; α-cellulose was put into 64% sulfuric acid solution in a certain proportion and stirred evenly at 40°C for 45 minutes, and a certain proportion of distilled water was added to terminate the reaction; then, nanocellulose suspension was obtained after dialysis, ultrasonic dispersion and centrifugation, and finally, bamboo nanocellulose was obtained after freeze-drying.
3. The high-adhesion tile adhesive according to claim 1, characterized in that: The particle size of the quartz sand is 200-300 meshes.
Citation Information
Cited By
Multifunctional ceramic tile adhesive and preparation method thereof
CN120717755A